Peningkatan Level Pemahaman Konsep Teori Kinetik Gas Mahasiswa Calon Guru Fisika Melalui Metode Demontrasi Interaktif dengan Bantuan Ragam Media Visual - Yusal, Yulianti; Suhandi, Andi; Setiawan, Wawan; Kaniawati, Ida (Universitas Nurul Huda, 2021)
The research on increasing the level of understanding of the kinetic theory of gases concepts for prospective physics teacher students through interactive demonstration methods with the help of a variety of visual media has been carried out. This study aims to determine the increase in the level of students’ understanding of the kinetic theory of gases concept through interactive demonstration methods with the help of various visual media. The method used was pre-experimental with one group pretest-posttest design. The research subjects were 76 prospective physics teacher students at a university in the city of Makassar, South Sulawesi. The test instrument used was a concept understanding level test in the form of an essay consisted of three questions. The results showed that most of the students reached a complete understanding level of the kinetic theory of gases after attending a basic physics course through interactive demonstration methods with the help of various visual media. Thus, the level of students’ understanding of kinetic theory of gases concept has increased through interactive demonstration methods with the help of various visual media.